Reduced audiovisual temporal sensitivity in Chinese children with dyslexia - Wu, Huiduo; Lu, Haidan; Lin, Qing; Zhang, Yuhong; Liu, Qiaoyun (Frontiers in Psychology, 2023)
Background: Temporal processing deficits regarding audiovisual cross-modal stimuli could affect children’s speed and accuracy of decoding. Aim: To investigate the characteristics of audiovisual temporal sensitivity (ATS) in Chinese children with and without developmental dyslexia and its impact on reading ability. Method: The audiovisual simultaneity judgment (SJ) and temporal order judgment (TOJ) tasks were performed to investigate the ATS of 106 Chinese children (53 with dyslexia) aged 8 to 12 and 37 adults without a history of dyslexia. The predictive effect of children’s audiovisual time binding window (TBW) on their reading ability and the effects of extra cognitive processing in the TOJ task on participants’ ATS were also investigated. Outcomes and results: With increasing inter-stimulus intervals (ISIs), the percentage of synchronous responses in adults declined more rapidly than that of children. Adults and typically developing children have significantly narrower TBWs than dyslexic children. The size of visual stimuli preceding auditory stimuli (VA) TBW had a marginally significant predictive effect on children’s reading fluency. Compared with the SJ task, the extra cognitive processing of the TOJ task affected children’s ATS. Conclusion and implications: The ATS of 8–12-year-old Chinese children is immature. Chinese dyslexic children have lower ATS than their peers.